Natural Resource Potential as a Driver of the Local Economy in Lantebung Tourism Village - Asya Karima (Wonderful-Journal of Tourism Destination, 2026)
This study explores the potential of natural resources as a driver of local economic development in Lantebung Tourism Village, Makassar, South Sulawesi. Using a qualitative method involving interviews, observations, and document analysis, the research examines how the mangrove ecosystem supports sustainable tourism initiatives. Findings indicate that the mangrove forest plays a dual role as an ecological asset and a tourist attraction, contributing to increased community income. However, community participation remains limited, with active involvement found only in a few areas such as ticketing and parking services. The former community-based initiatives like Pokdarwis and mangrove crab cultivation have become inactive due to limited awareness, training, and funding. The study recommends revitalizing community institutions, establishing structured capacity-building programs, and creating funding mechanisms through partnerships. The research contributes to the understanding of how nature-based tourism can drive local economies and highlights the importance of empowerment for sustainability.